Genotypic Variability, Correlation and Path Coefficient Analysis for Elite Genotypes of Chickpea (Cicer arietinum L.) - Pravalika, Yellanki; Aggarwal, Nikita; Kumar, Rajneesh; Tutlani, Aman; Parveen, Shama; Rathore, Mukesh (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted during the rabi season (October, 2021–April, 2022) at the Crop Research Centre, Department of Genetics and Plant Breeding, School of Agriculture, ITM University, Gwalior, Madhya Pradesh, focused on 30 chickpea genotypes to evaluate genetic variability, heritability, genetic advance, correlations and path analysis among quantitative traits. Utilizing a randomized block design, the study found that the number of pods plant-1 exhibited the highest variability, while pod length showed the least variability. Significant phenotypic and genotypic coefficients of variation highlighted substantial variability among the genotypes, with shoot length, root length, and the number of secondary branches displaying high genetic advance and heritability. This suggested the predominant influence of additive gene action on these traits, making them suitable for selection-based improvements. Genotypic and phenotypic correlations were generally similar, indicating minimal environmental influence on most traits. Positive correlations were identified between the number of primary branches, number of secondary branches, pods plant-1, seeds pod-1, seed index and other dependent traits, indicating their potential for enhancing crop yield through selection. The study further revealed significant direct associations among traits, emphasizing the presence of additive gene action and the feasibility of effective selection for improving chickpea characteristics. In conclusion, the findings offer valuable insights into the genetic variability and heritability of chickpea traits, guiding future breeding and selection programs for enhanced genotypes.